Sistem Pakar Mendiagnosa Penyakit pada Ikan Nila dengan Metode Vcirs - Yuliana Sera Bora; Cecilia D.P.B Gabriel; Maria Wilda Malo (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
An expert system for diagnosing diseases in tilapia is one solution to help fish farmers detect and treat diseases that attack tilapia. In this study, an expert system was developed using the VCIRS (Voting Classifier for Integrated Rule Set) method to diagnose tilapia diseases based on the symptoms shown. The VCIRS method was chosen because of its ability to combine several classifiers to improve diagnostic accuracy. This system allows users, especially fish farmers, to enter symptoms observed in tilapia and obtain a diagnosis of possible diseases and appropriate treatment recommendations. The evaluation results showed that this system has a good level of accuracy in diagnosing tilapia diseases, by providing fast and accurate results, and making it easier for fish farmers to make decisions related to fish health. This expert system is expected to increase the productivity of tilapia cultivation by reducing the mortality rate of fish due to diseases that are not detected quickly.